POVERTY FACTOR ANALYSIS AND ECONOMIC GROWTH AGAINST THE INDEX HUMAN DEVELOPMENT (IPM) IN PADANGSIDIMPUAN CITY - Abdelina, Abdelina; Saryani, Lilis (Journal of Industrial Engineering & Management Research, 2021)
This research aims to learn about poverty in Padangsidimpuan City while also comparing the economy to the Human Development Index. This study is divided into two categories: research documents and library research (Library Research). The approach used in this research is a quantitative method that uses panel data and a fixed effect model; the measures in this study are secondary data collection from the Central Statistics Agency after data review. Based on the findings of the study, using the Fixed Effects Model Analysis method, a negative variable is generated on the Human Development Index in Padangsidimpuan City, when comparing the Economy associated with the Human Development Index in Padangsidimpuan City. Although poverty and published economics linked to the Human Development Index in Padangsidimpuan City are both visible.